The Importance of Analysis of Judicial Circumstances in the Sentence Dosimetry Process: A Importância Da Análise Das Circunstâncias Judiciais No Processo De Dosimetria Da Pena - Da Silva, Cliciano; De Moura Lino, Janildes (International Journal of Scientific Research and Management (IJSRM), 2024)
The Constitution plays an important role as a point of reference for the critical analysis of the criminal system, not only because it derives from the legal assets susceptible to punitive protection, but also and among other reasons, because the principles enshrined as a government norm in the Penal Code governing The imposition of sanctions is a clear development of the constitutional text and doctrine that the Constitutional Court has been building with its pronouncements, in the form that criminal law must acquire. The dosimetry of punishment in Brazil takes a three-step approach, pushing the system of fixed sanctions implemented by the legislature or the full discretion of the judge, promoting, on the other hand, a distribution of functions between the two, as he chooses the minimum and maximum sentence levels and dosage parameters, and this determines the sanction in the specific case from the legal criteria. In this sense, the present research aims to analyze the importance of analyzing judicial circumstances in the process of penalty dosimetry. The specific objectives are: to present a brief history of criminal legislation in Brazil, to review the most recent literature on the application of the penalty and its principles, to analyze the relationship between the dosimetry of the penalty and judicial circumstances and to point out cases in the jurisprudence that materialize the revised theory. Thus, given the relevance of the theme in the current legal scenario, the research is justified by discussing a contemporary theme. Through research on the principles of exceptionality, state of innocence, motivation of decisions and proportionality and the dosimetry of the penalty, possible judgments of the judge that relate the dosimetry of the penalty with the principles of human rights will be discussed. The judge should take charge of the evidence produced in relation to the facts that, in his opinion, influence the minor or major measure of the exact penalty to be imposed. The lack of motivation currently constitutes a violation of the constitutional guarantee of due process and absolute grounds for invalidity under the Criminal Procedure Code.